Analysis of a Tramcar Ride when Passing a Point Frog and when Entering Small Radius Arc by Specific Rail Geometry - Hauser, Vladimír; Kravchenko, Kateryna; Loulová, Mária; Nozhenko, Olena; Fomin, Oleksij (Manufacturing Technology Journal, 2019)
In urban railway environments, in many respects, the problem of tramcars passing small radius arches appears to be topical. In this regard, the authors proposed that the wheelsets should be complemented on the outer side of the wheels with a second tread of a lower radius, intended exclusively for ride in arches of the track with a radius which the conventional wheelsets cannot even theoretically pass without creep (subject of patent application a201701589). The complemented wheel tread enters into operation (or out of action) as a result of passing over a specially shaped rail located in the intersections before and behind the small radius arc. In this process, there is a change in the wheel-rail contact location - similar to what is commonly used when riding on a facing rail located in the immediate vicinity of the point frog. The paper deals with the comparison of these two cases based on a simulation analysis of vehicle ride in the calculation program.
Keywords: rail-wheel contact point relocation; point frog; double tread; small radius track